A Comparative Study on Data Augmentation Using Generative Models for Robust Solar Irradiance Prediction - Jinyeong Oh(오진영); Jimin Lee(이지민); Daesungjin Kim(김대성진); Bo-Young Kim(김보영); Jihoon Moon(문지훈) (한국컴퓨터정보학회논문지, 2023)
In this paper, we propose a method to enhance the prediction accuracy of solar irradiance for three major South Korean cities: Seoul, Busan, and Incheon. Our method entails the development of five generative models—vanilla GAN, CTGAN, Copula GAN, WGANGP, and TVAE—to generate independent variables that mimic the patterns of existing training data. To mitigate the bias in model training, we derive values for the dependent variables using random forests and deep neural networks, enriching the training datasets. These datasets are integrated with existing data to form comprehensive solar irradiance prediction models. The experimentation revealed that the augmented datasets led to significantly improved model performance compared to those trained solely on the original data. Specifically, CTGAN showed outstanding results due to its sophisticated mechanism for handling the intricacies of multivariate data relationships, ensuring that the generated data are diverse and closely aligned with the real-world variability of solar irradiance. The proposed method is expected to address the issue of data scarcity by augmenting the training data with high-quality synthetic data, thereby contributing to the operation of solar power systems for sustainable development. KCI Citation Count: 0